(untitled) (Epidemiology, Biostatistics, and Public Health, 2023)
Background: Overweight and obesity has become a serious public health problem in the world. Changes in daily physical activity (PA) levels may help moderate the health risks of sedentary behavior (SB). The aim of the present study was to determine PA and SB by triaxial accelerometer (ActiGraph GTX3 GT3X+, ActiGraph, Pensacola, FL. 32502 USA) in Syrian adults that affected by age, marital, body mass index (BMI), education, and smoking status. Methods: We used cross-sectional baseline data from 97 participants of adults (18-60 years). Subjects wore an accelerometer for 7 consecutive days. Magnitude counts/minute was extracted to determine time in inactivity, in low-intensity, moderate, and vigorous-to-very-vigorous activity. Results: Higher age was associated with more time in all categories of PA (light, moderate vigorous MVPA with bouts, MVPA without bouts, and step per day), while higher BMI was related to less time in PA, overweight/obese subjects, on daily average, spent less, but not significantly, time standing and little more time spent in sitting than the normal weight groups. Participant comparing to non-smoking peoples tended to spent less time in PA; however, this synchronization was not considerable. Conclusion: Finally, our investigation demonstrated a positive synchronization between sedentary time and educational level. In this cohort of adults, most of men and women fulfilled the WHO recommendations. The levels of PA in 18–60-year-old adults are similar to previous data reported in adults.